How Magnetically Conjugate Atmospheres and the Magnetosphere Participate in the Formation of Low‐Energy Electron Precipitation in the Region of Diffuse Aurora. Issue 8 (28th July 2020) - Khazanov, George V.; Glocer, Alex
Abstract: The electron precipitation in the region of the diffuse aurora should be considered as a two‐step process (Khazanov et al., 2017, https://doi.org/10.1002/2016GL072063 ). The first one is the interaction of plasma sheet electrons with electrostatic electron cyclotron and/or whistler waves, moving those electrons into the loss cone to precipitate in both magnetically conjugate atmospheres. The second step is the interaction of these electrons with the ionosphere and atmosphere via their elastic and nonelastic collisions and reflection (backscatter) of degraded electrons back to magnetosphere and conjugate ionospheres. This paper presents the results of a newly developed scenario of nonsteady‐state electron precipitation dynamics that accounts for magnetosphere‐ionosphere‐atmosphere energy interplay over the entire energy range of the plasma sheet electron population and their affiliated secondary electrons. It also studies how both magnetically conjugate auroral regions work together with the magnetosphere in the formation of electron precipitation in the region of the diffuse aurora with the energy range coverage from 1 eV up to 10 keV. Key Points: The electron precipitation in the region of the diffuse aurora should be considered as a two‐step process Newly developed scenario of nonsteady‐state electron precipitation dynamics is discussed Asymmetry and MI coupling play a role in the formation of low energy electron precipitation